KARAKTERISTIK KIMIA DAN AKSEPTABILITAS KERUPUK BERAS MERAH DENGAN PENAMBAHANTEPUNG WORTEL SUBSTANDAR - Hafidzi, Marlan; Quddus, Ati Atul; ., Mardiana (Universitas Muhammadiyah Semarang, 2024)
Red rice crackers are a type of snack made from red rice and tapioca, with additional nutrients derived from substandard carrots. Substandard carrots that can still be utilized include broken carrots, irregular sizes, post-harvest defects, and branched roots, which are processed into flour to facilitate their use. This research aims to determine the effect of the addition of carrot flour on the chemical properties, and acceptability of red rice crackers, and the best treatment based on chemical properties and acceptability. The method used is a Completely Randomized Design (CRD) single factor with treatments using red rice flour compared to carrot flour P1 (90%:10%), P2 (80%:20%), P3 (70%:30%), P4 (60%:40%). Based on the research results, the addition of carrot flour significantly affects the ash content, fat content, protein content, color, aroma, taste, texture, and total acceptance but does not significantly affect the water content and carbohydrate content. The best red rice crackers are obtained from treatment P1 (90% red rice flour: 10% carrot flour) with chemical values of water content 2.06% (db), ash content 3.16% (db), fat content 2.97% (db), protein content 9.65% (db), carbohydrate content 84.22% (db), and acceptability values of color 1.57 (very like), aroma 1.87 (very like), taste 1.53 (very like), texture 1.80 (very like), and total acceptance 1.47 (very like).